2001
DOI: 10.1084/jem.194.7.915
|View full text |Cite
|
Sign up to set email alerts
|

Deficiency of Small Gtpase Rac2 Affects T Cell Activation

Abstract: Rac2 is a hematopoietic-specific GTPase acting as a molecular switch to mediate both transcriptional activation and cell morphological changes. We have examined the effect of Rac2 deficiency during T cell activation. In Rac2−/− T cells, proliferation was reduced upon stimulation with either plate-bound anti-CD3 or T cell receptor–specific antigen. This defect is accompanied with decreased activation of mitogen activated protein kinase extracellular signal–regulated kinase (ERK)1/2 and p38, and reduced Ca2+ mob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
84
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 101 publications
(92 citation statements)
references
References 64 publications
8
84
0
Order By: Relevance
“…However, the inverse localization of pERK staining within plasma membrane lipid rafts in primed but not tolerized cells might suggest that Rap1 antagonism of ERK activation could also reflect disruption and termination of productive synapse formation and signaling. Consistent with this, recent reports have indicated that ERK is an intermediate signal in the Vav/Rac2-mediated pathway (69), leading to nucleation of actin filaments and cytoskeleton remodeling at the immunological synapse (70). Thus, partitioning of Fyn and Lck and the consequent generation of the negative regulatory complex comprising Fyn, PAG, and Csk (71,72), might be required for compartmentalization and rewiring of Rap1 signaling via the assembly of the Fyn-Cbl-CrkL-C3G-Rap1 complex (73)(74)(75), that is found to be selectively expressed in tolerized cells (17).…”
Section: Discussionsupporting
confidence: 76%
“…However, the inverse localization of pERK staining within plasma membrane lipid rafts in primed but not tolerized cells might suggest that Rap1 antagonism of ERK activation could also reflect disruption and termination of productive synapse formation and signaling. Consistent with this, recent reports have indicated that ERK is an intermediate signal in the Vav/Rac2-mediated pathway (69), leading to nucleation of actin filaments and cytoskeleton remodeling at the immunological synapse (70). Thus, partitioning of Fyn and Lck and the consequent generation of the negative regulatory complex comprising Fyn, PAG, and Csk (71,72), might be required for compartmentalization and rewiring of Rap1 signaling via the assembly of the Fyn-Cbl-CrkL-C3G-Rap1 complex (73)(74)(75), that is found to be selectively expressed in tolerized cells (17).…”
Section: Discussionsupporting
confidence: 76%
“…The Vav/Rac pathway cooperates with RasGRP1 for optimal activation of Ras To start dissecting the signaling relationships between the Vav/Rac and Ras pathways during T-cell stimulation, we made use of previous observations with knockout animals demonstrating that the disruption of vav and rac2 genes affects negatively the activation of PLC-g (Costello et al, 1999;Yu et al, 2001). Moreover, we and others have observed that, in vav3 (À/À) chicken B cells, there is no proper stimulation of the Ras pathway upon B-cell receptor activation, a defective response derived from defective PLC-g activation (Inabe et al, 2002;Caloca et al, 2003b).…”
Section: Resultsmentioning
confidence: 99%
“…Likewise, Vav can trigger the induction of Rasdependent responses when overexpressed in Jurkat cells (Villalba et al, 2000b). These effects appear to be Rac dependent, since rac2 (À/À) T cells also have some defects in Erk activation (Yu et al, 2001). Despite this evidence, the mechanism that mediates the interconnection between the Vav/Rac pathways and the Ras route in T cells remains unknown up to know.…”
Section: Introductionmentioning
confidence: 99%
“…All these different processes require energy, with the result of the up-regulation of the cytochrome c oxidase, subunit VIIc gene. Other genes such as the histamine receptor H2, the interferon-inducible GTPase, the guanine nucleotide binding protein, and T-cell specific GTPase are related to immune response and intracellular signal transduction [24][25][26].…”
Section: Discussionmentioning
confidence: 99%